Factors affecting customers acceptance towards 1Aslah personal financing-i offered by Bank Rakyat Tawau / Siti Hasmah Hamri - Hamri, Siti Hasmah (2011)
This study is conducted for the purposes to identify the factors affecting customers' acceptance towards 1Aslah personal financing-i and to provide useful recommendation to Bank Rakyat Tawau towards 1Aslah personal financing-i. Besides that, the other objective is to identify factors that influence muslim and non-muslim customers in selecting 1Aslah personal financing-i product. The customers' acceptance is depending on five factors in Bank Rakyat which include religious obligation, fast and efficient service, advertisement marketing, knowledge-of the product and employees of bank are politely and friendly. Most importantly, this study considers establishing a specific rank of factors selection for 1Aslah personal financing-i. The sample comprised of 100 customers of Bank Kerjasama Rakyat Malaysia Berhad Tawau. Data were obtained through a face-to-face survey using questionnaire. This study used reliability analysis, frequency analysis, descriptive statistic, cross tabulation and friedman test to analyse the data. Overall, the results or analysis showed that this study had achieved the objectives of the research. Based on the finding and analysis "the loan approval only takes a short time to be approved", "staff willingness to help the customer regarding their problems in personal loan", "a creative brochure will make people interested and aware with the product", "Islamic personal financing must be based on the Quran and Sunnah as the sources" and "bank give customer individual attention by giving advice about the loan" are the first five factors selection considered as being very important. The least preferred factor among others are "most of people know the information from the advertisement marketing which is from newspaper, television and radio'. Hence, more effective strategies can be recommended to attract bank customers to use 1Aslah personal financing-i at Bank Rakyat Tawau.